THE EFFECT OF PHYSICAL WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT SIGAP DASA PERKASA IN SOUTH JAKARTA - Desi Prasetiyani; Endang Kustini; Ratna Sari (International Journal Multidisciplinary Science, 2025)
This study examines the influence of the physical work environment and work discipline on employee performance at PT Sigap Dasa Perkasa. The research employs a quantitative associative approach, utilizing survey methods with data collected through questionnaires, interviews, and observations. The sample consists of employees selected through purposive sampling, and data analysis was conducted using multiple regression analysis. The physical work environment was evaluated based on lighting, air circulation, cleanliness, and overall workplace comfort, while work discipline was assessed in terms of attendance, adherence to rules, and accountability. Employee performance was measured through work quality, quantity, punctuality, and independence. The findings indicate that both physical work environment and work discipline significantly affect employee performance. A conducive work environment enhances focus and productivity, while strong discipline fosters consistency, responsibility, and efficiency. The study concludes that optimizing workplace conditions and implementing structured disciplinary policies can enhance overall employee performance. It is recommended that PT Sigap Dasa Perkasa continuously improve workplace facilities and maintain a culture of discipline to achieve sustainable productivity and competitiveness.